2021
DOI: 10.7554/elife.66488
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of ASIC1a delineates conformational signaling from proton-sensing domains to the channel gate

Abstract: Acid-sensing ion channels (ASICs) are neuronal Na+ channels that are activated by a drop in pH. Their established physiological and pathological roles, involving fear behaviors, learning, pain sensation and neurodegeneration after stroke, make them promising targets for future drugs. Currently, the ASIC activation mechanism is not understood. Here we used voltage-clamp fluorometry (VCF) combined with fluorophore-quencher pairing to determine the kinetics and direction of movements. We show that conformational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Figure 2D and E, 3D and E). While non-apparent openings suggested by the linear gating model ( 14) could explain changes in fluorescence at moderate pH, we deem it more likely that these fluorescence changes are a result of protonation events in the ECD that primarily lead to SSD in a model supported by others (19,20). Disruption of the swiveling motion of the β11-12 linker via the N4141K mutation thus limited acute desensitization and SSD, but the dynamic conformational changes of the upper and mid-ECD appeared largely retained (Figure 2E and 3E).…”
Section: Conformational Changes In Ecd and Upper Tmd Are Associated W...mentioning
confidence: 64%
See 2 more Smart Citations
“…Figure 2D and E, 3D and E). While non-apparent openings suggested by the linear gating model ( 14) could explain changes in fluorescence at moderate pH, we deem it more likely that these fluorescence changes are a result of protonation events in the ECD that primarily lead to SSD in a model supported by others (19,20). Disruption of the swiveling motion of the β11-12 linker via the N4141K mutation thus limited acute desensitization and SSD, but the dynamic conformational changes of the upper and mid-ECD appeared largely retained (Figure 2E and 3E).…”
Section: Conformational Changes In Ecd and Upper Tmd Are Associated W...mentioning
confidence: 64%
“…To this end, we labeled the channel in two more positions previously reported to yield changes in fluorescence signals, E425C and H72C (Figure 4A, Suppl. Figure S4A) (19, 40, 45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional observations indicate that ASIC1a is activated by H + -induced allosteric changes 40 . Further support for an allosteric activation mechanism came from voltage-clamp fluorometry experiments which showed evidence for conformational changes linked to ASIC1a activation 27, 28, 29, 30 and from the observation that mutation of the two residues involved in ASIC1a pore block by Ca 2+ did not abolish pH-dependent gating 17 . The E425G mutation decreased the Ca 2+ -induced shift of the pH dependence of SSD, while D432C decreased the Ca 2+ -induced shift of the activation pH dependence 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A study with toadfish ASIC1 also found a competition between H + and Ca 2+ and concluded, based on a detailed functional analysis, that this channel is activated by an allosteric mechanism and not by a release of Ca 2+ block [32]. A further indication that in ASIC1a, activation involves conformational changes comes from voltage clamp fluorometry studies that detected conformational changes associated with channel opening [33,34].…”
Section: Discussionmentioning
confidence: 99%